Serbia - Spending for Justice : A Judicial Public Expenditure and Institutional Review - World Bank (World Bank, Washington, DC, 2018)
Reform of the judiciary is a key element of Serbia’s European Union (EU) accession process, and in ensuring sustainable economic growth and delivering justice to Serbian citizens and businesses. Reform of the judiciary has been ongoing since the regime change in 2000. However, efforts accelerated in the more stable and pro-European political environment after 2008.